Pengembangan Learning Management System Terintegrasi Project Based Learning Untuk Mendukung Hasil Belajar Pada Materi Konfigurasi Routing(Studi Kasus Siswa Kelas Xi Tjkt Smkn 1 Kediri) - Husna Lathifunisa Arif; Harun Al Rosyid (Jurnal Ilmu Teknologi Informasi Indonesia, 2026)
This study is motivated by students' low learning outcomes in the subject matter, caused by suboptimal teaching methods and a lack of interactive media to support independent networking practice. This research aims to develop a Moodle-based Learning Management System (LMS) named "SmeksaRoute," integrated with Project-Based Learning (PjBL), to improve student learning outcomes in the Routing Configuration subject at SMKN 1 Kediri. This study employs a Research and Development (R&D) approach using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model, along with a quasi-experimental research design to determine the effectiveness of the developed product. The research subjects consisted of 68 students divided into two groups: a control class (34 students) applying the existing teaching method, and an experimental class (34 students) utilizing "SmeksaRoute". Practical sessions were conducted through GNS3 network simulation using MikroTik RouterOS devices. The analysis results indicate that "SmeksaRoute" falls into the "highly valid" category, with validation scores reaching 94% for media, 88% for teaching modules, 88% for learning materials, and 94% for assessment questions. The learning outcome data were analyzed using the Shapiro-Wilk normality test and Levene's test for homogeneity, followed by the Mann-Whitney U hypothesis test due to non-normally distributed data. The average posttest score for the control class was 71.18, whereas the experimental class achieved 78.68. The significance value from the Mann-Whitney U Test was 0.0004428 (< 0.05), indicating a significant difference between the two classes. Overall, "SmeksaRoute," as a PjBL-integrated LMS for the Routing Configuration subject, has proven to be both valid and effective in improving student learning outcomes.